Reduced-Precision Redundancy on FPGAs - Brian Pratt; Megan Fuller; Michael Wirthlin (International Journal of Reconfigurable Computing)
Reduced-precision redundancy (RPR) has been shown to be a viable alternative to triple modular redundancy (TMR) for digital circuits. This paper builds on previous research by offering a detailed analysis of the implementation of RPR on FPGAs to improve reliability in soft error environments. Example implementations and fault injection experiments demonstrate the cost and benefits of RPR, showing how RPR can be used to improve the failure rate by up to 200 times over an unmitigated system at costs less than half that of TMR. A novel method is also presented for improving the error-masking ability of RPR by up to 5 times at no additional hardware cost under certain conditions. This research shows RPR to be a very flexible soft error mitigation technique and offers insight into its application on FPGAs.